(3OdGFd GdNjQGJ hThGQb GdCfhGQ aj PcQ GdUdGI Ydi GdfHj GdeNJGQs - (3GdLRhdj, eMeO Hf SdjeGf Hf YHO GdQMef, J(B870(3g`s
(3ChdgG (B:s
(3fGbU GdChdhCUMGHg GdfLHGAhSejJg HcJGH OdGFd GdNjQGJ hThGQb GdCfhGQ aj PcQ GdUdGI Ydi GdfHj GdeNJGQs
(3BNQgG (B:s
(3fGbU GdBNQ, hBNQg(B: (3GdebQHjf GdPjf jSHMhf Gddjd hGdfgGQ dG jaJQhf hdG jYUhf Gddgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 6 / 151s
(3eYLe GdeDdajf(B: 3 / 333s
(3cTa GdXfhf(B: 1 / 759s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJUha hGdBOGH GdTQYjIs